The Outcome of Concurrent Intracameral Fluconazole Injection with Amniotic Membrane Transplantation for Fungal Keratitis in Dr. M. Djamil General Hospital: A Case Series - Ferry Indratno; Havriza Vitresia (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Fungal keratitis is often difficult to eradicate and requires long treatment. Antifungal agents have lower efficacy because of low tissue penetration and the indolent nature of the infection. Fluconazole has effective ocular penetration ability, reaching aqueous concentration as same as plasm concentration. Multilayer amniotic membrane transplantation (MLAMT) has been shown to be a promising surgical procedure to reconstruct the ocular surface by supporting the epithelialization of the cornea and having protective antimicrobial properties. This study aims to report the outcome of concurrent intracameral fluconazole injection with amniotic membrane transplantation for fungal keratitis in Dr. M. Djamil General Hospital. Case presentation: Four inpatients in the ophthalmology ward of Dr. M. Djamil General Hospital with moderate to severe fungal keratitis. All patients were first treated with medications. Because the patients did not show clinical improvement after getting maximum therapy, they underwent intracameral fluconazole injection concurrent with MLAMT. MLAMT was performed with multilayered amniotic membranes to fill and cover the defect. The bandage contact lens was placed to protect and keep the MLAMT in place and for patients’ comfort. Patients were then observed for signs of inflammatory reaction and epithelialization. All patients showed reduced inflammation and improved epithelization after surgery. Conclusion: Concurrent intracameral fluconazole injection with MLAMT can be considered an alternative treatment for refractory fungal keratitis as it decreases the rate of inflammation and improves epithelization.